O processo de aprendizagem em práticas de ensino por investigação: interpretações a partir da abordagem fenomenológica e semiótica social - Bocanegra, Carlos Henrique [UNESP] (2015)
This research of qualitative trait was planned and developed in a classroom with high school students of a public school. It involved the development and implementation of a plan of didactic activities focused on inquiry teaching. Its objective was to analyze how subjects conceive learning of scientific contents, among others, and associate it to socio-scientific issues related to the topics studied in the projects developed by their teams in the discipline Scientific-Technical Projects (STP). Firstly, their descriptions were collected in different stages of the work. After that, their perceptions about learning were raised and analyzed the theoretical and methodologial framework proposed by the Phenomenology (phenomenological approach based on the phenomenological method of Giorgi) and social Semiotics. The results show that students lead their learning through dialogue among them with the help of the teacher. We also observed that, in many of these situations occurred during the stages of the project, the motivational aspects, dedication and attention given to the work preparation process were highlighted by the students, which helped them take it as a reference for future projects, which could be realized by them at different of schooling. In summary, we emphasize that for the most of the subjects, the act of learning poved to be a challenge because of the complexity and extent of the proposed work to STP. In addition, it is worthy highlighting that the understanding of what learning is was expressed through the semiotic formations raised, converging on the following statement proposed by the researcher: a way, a path, finally, above all, a stream of activities to be methodically developed by the students, based on motivation, attention, dedication and critical sense, like the steps of the investigative work in STP, so that stream enables the learner to incorporate them (activities) gradually in the knowledge domain, in order to use...